Microbiota and enteric nervous system crosstalk in diabetic gastroenteropathy: bridging mechanistic insights to microbiome-based therapies - Tao, Wang; Yu, Yunfeng; Tan, Danni; Huang, Xiangning; Huang, Jiawang; Lin, Chuanquan; Yu, Rong (Frontiers in Cellular and Infection Microbiology, 2025)
Diabetes mellitus has emerged as a global public health crisis, with over half of patients experiencing gastrointestinal (GI) symptoms that exacerbate glucose fluctuations and impair quality of life. While prior research on the pathophysiology of diabetic gastroenteropathy (DGE) focused primarily on autonomic neuropathy, particularly involving the vagus nerve, recent studies have shifted toward the impairment of the enteric nervous system (ENS). As the largest autonomous neural network governing GI motility independent of central control, structural and functional abnormalities of the ENS constitute the fundamental pathological basis for DGE. This review first delineates gut microbial alterations in diabetes and mechanisms by which dysbiosis compromises the integrity of the ENS. Second, we analyze how microbiota-derived metabolites (short-chain fatty acids, bile acids, tryptophan), gut hormones (glucagon-like peptide-1, ghrelin), and neurotransmitters (acetylcholine, vasoactive intestinal peptide, nitric oxide) multitarget the ENS—collectively establishing the “microbiota-ENS axis” as the central hub for GI sensorimotor control. Finally, we provide an overview of preclinical and clinical evidence for microbiome-targeted therapies (probiotics, prebiotics, fecal microbiota transplantation) in alleviating DGE symptoms and repairing ENS while outlining translational challenges and future research priorities.